Placental glucocorticoid receptor isoforms in a sheep model of maternal allergic asthma. (August 2019) - Clifton, Vicki L.; McDonald, Megan; Morrison, Janna L.; Holman, Stacey L.; Lock, Mitchell C.; Saif, Zarqa; Meakin, Ashley; Wooldridge, Amy L.; Gatford, Kathryn L.; Wallace, Megan J.; Muhlhausler, Beverly S.; Bischof, Robert J.; et al.
Abstract: Maternal asthma increases the risk of adverse pregnancy outcomes and may affect fetal growth and placental function by differential effects on the expression of glucocorticoid receptor (GR) isoforms, leading to altered glucocorticoid signalling. Our aim was to examine the effect of maternal asthma on placental GR profiles using a pregnant sheep model of asthma. Nine known GR isoforms were detected. There was a significant increase in the expression of placental GR isoforms that are known to have low trans-activational activity in other species including GR A, GR P and GRγ which may result in a pro-inflammatory environment in the presence of allergic asthma. Highlights: Sheep placenta contains 9 different glucocorticoid receptor (GR) isoforms GR isoform expression varies in relation to placentome type Low transactivational GR isoforms predominate in the presence of a sheep model of maternal allergic asthma